A Bibenzyl Component Moscatilin Mitigates Glycation-Mediated Damages in an SH-SY5Y Cell Model of Neurodegenerative Diseases through AMPK Activation and RAGE/NF-κB Pathway Suppression - Mei Chou Lai; Wayne Young Liu; Shorong-Shii Liou; I-Min Liu (Molecules, 2020)
Moscatilin can protect rat pheochromocytoma cells against methylglyoxal-induced damage. Elimination of the effect of advanced glycation end-products (AGEs) but activation of AMP-activated protein kinase (AMPK) are the potential therapeutic targets for the neurodegenerative diseases. Our study aimed to clarify AMPK signaling’s role in the beneficial effects of moscatilin on the diabetic/hyperglycemia-associated neurodegenerative disorders. AGEs-induced injury in SH-SY5Y cells was used as an in vitro neurodegenerative model. AGEs stimulation resulted in cellular viability loss and reactive oxygen species production, and mitochondrial membrane potential collapse. It was observed that the cleaved forms of caspase-9, caspase-3, and poly (ADP-ribose) polymerase increased in SH-SY5Y cells following AGEs exposure. AGEs decreased Bcl-2 but increased Bax and p53 expression and nuclear factor kappa-B activation in SH-SY5Y cells. AGEs also attenuated the phosphorylation level of AMPK. These AGEs-induced detrimental effects were ameliorated by moscatilin, which was similar to the actions of metformin. Compound C, an inhibitor of AMPK, abolished the beneficial effects of moscatilin on the regulation of SH-SY5Y cells’ function, indicating the involvement of AMPK. In conclusion, moscatilin offers a promising therapeutic strategy to reduce the neurotoxicity or AMPK dysfunction of AGEs. It provides a potential beneficial effect with AGEs-related neurodegenerative diseases.